If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -72x + -9y + -72 = 0 Reorder the terms: -72 + -72x + -9y = 0 Solving -72 + -72x + -9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72' to each side of the equation. -72 + -72x + 72 + -9y = 0 + 72 Reorder the terms: -72 + 72 + -72x + -9y = 0 + 72 Combine like terms: -72 + 72 = 0 0 + -72x + -9y = 0 + 72 -72x + -9y = 0 + 72 Combine like terms: 0 + 72 = 72 -72x + -9y = 72 Add '9y' to each side of the equation. -72x + -9y + 9y = 72 + 9y Combine like terms: -9y + 9y = 0 -72x + 0 = 72 + 9y -72x = 72 + 9y Divide each side by '-72'. x = -1 + -0.125y Simplifying x = -1 + -0.125y
| 3/25x=-1/5 | | 64x^4-16x^2+1=0 | | 10000/.05 | | y+3(y-1)-1=44 | | A=q+qsh | | -6*-6+12/-24= | | sqr(x+12)=x | | 9.02x+3.59(8x-4)=12.03x+0.5612 | | sqr(x+12)=x | | ab+2b=6 | | 3n+(9+3)=15 | | 4(m-6)=7m | | 7c/3=25 | | 495/4000 | | 11x+14z=32 | | 18x+16=18x-16 | | sqr(126-10x)=2x | | 0=24x+6 | | 10+0.75Y=10+0.75y | | 5x-2z=32 | | 11(t-6)+7t=6(3t+5)-8 | | 338=(x)(2x) | | 26n-31n-6n-5n-25n-12=-6 | | ln(3x-1)=ln(x-6) | | 15x-8=12+25 | | 10x-x=40 | | 4[9-(6x-3)]+6x=0 | | y=10sin^2 | | -2x^2+1=17 | | 3+5(5t+1)= | | x^5-7x^4+2x^3-x^2-6x+15=0 | | x-(x*0.05)=25831.29 |